Utilization of central nervous system resources for preparation and performance of complex walking tasks in older adults - Clark, David J.; Rose, Dorian K.; Ring, Sarah A.; Porges, Eric C. (Frontiers in Aging Neuroscience, 2014)
Introduction Walking in the home and community often involves performance of complex walking tasks. Understanding the control of such tasks is crucial to preserving independence and quality of life in older adults. However, very little research has been conducted in this area. Here we assess the extent to which two measures of central nervous system (CNS) activity are responsive to the challenges posed by preparation and performance of complex walking tasks. Prefrontal cortical activity was measured by functional near infrared spectroscopy (fNIRS) and sympathetic nervous system arousal was measured by skin conductance level (SCL). Materials and Methods Sixteen older men and women (age 77.2 ± 5.6 years) with mild mobility deficits participated in this study. Participants walked at their preferred speed without distractions along an unobstructed, well-lit course (control task) and also walked on the same course under five separate challenging conditions: performing a cognitive verbal fluency task (verbal task), dim lighting (dim task), carrying a tray (carry task), negotiating obstacles (obstacles task) and wearing a weighted vest (vest task). Mean prefrontal activation and SCL were calculated during the preparation and performance phases of each task. Gait spatiotemporal measurements were acquired by an instrumented gait mat. Results Prefrontal cortical activity and SCL were elevated during the preparation phase of complex walking tasks relative to the control task. During the performance phase, prefrontal activity remained elevated to a similar level as during task preparation. In contrast, SCL continued to increase beyond the level observed during task preparation. A larger increase in prefrontal activity was found to be linked to preserved quality of gait during complex walking tasks. Discussion These findings indicate that availability and utilization of CNS resources are important for optimizing performance of complex walking tasks in older adults.